Argumentative structures and techniques in the school Discourse - Villanueva Chaucas, María Elena (2021)
This study suggests an interdisciplinary model for the analysis of school argumentation that applies the Theory of Argumentation to the educational field. For the reconstruction of the school argumentative discourse, two theoretical tools have been used: Lo Cascio’s (1998) textual linguistics —useful in order to discover the argumentative framework— and the new rhetoric of Perelman and Olbrechts-Tyteca (1958/1989), which will serve to recognize the argumentative techniques used. The method of this work is a qualitative research with descriptive orientation; the latter aspect can be seen in the systematic observation of the elements that make up the argumentation, the graphic representation of the arguments and the identification of the argumentative techniques used by the students in their dissertation. The evaluation of these data provides an understanding of the relationship between the arguments exposed and demonstrates the presence of reservations and reiterations of the point of view throughout their discourse; in addition, the use of connectors, reformulators and argumentative operators to point out the route taken by the propositions and finally, the argumentative techniques used are interpreted.